A temperature-adaptive thermoregulated radiative cooling coating, method of preparation and use thereof
Patent Information
- Application Number
- CN202511682265.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-17
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-11-17
AI Technical Summary
然而,上述材料仍处于研究阶段,迄今为止尚未投入商业使用
(1)本发明将辐射冷却技术与室温相变技术结合起来,相较于传统的辐射冷却器,本发明的材料可以缓解白天过热,夜间过冷的问题。通过控制不同原料比例合成了一个金属有机框架材料(MOF)zif-8,与未完全反应的ZnO粒子组成了ZnO@zif-8混合纳米粒子,混合纳米粒子制备的辐射冷却涂层实现了较高的太阳反射率(91.9%)和红外发射率(94.4%,8-13μm),规则多面体形态的ZnO@zif-8聚合物涂层显著增强了阳光的散射,于相变材料结合后实现了夜间平均下降0.66℃和中午平均下降9.8℃的亚环境冷却。该温度自适应的材料在被动辐射冷却调节方面显示出巨大的前景,可以进一步扩展被动辐射冷却的应用。
Smart Images

Figure CN121379290B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of radiation cooling coating preparation, and particularly to a temperature-adaptive thermally regulated radiation cooling coating, its preparation method, and its application. Background Technology
[0002] As the atmospheric greenhouse effect intensifies, global average temperatures will inevitably rise year by year, ultimately leading to global warming. Therefore, the need for cooling is constantly increasing. Traditional air conditioning not only consumes a large amount of energy but also releases large amounts of greenhouse gases, exacerbating the energy crisis and global warming. It is estimated that cooling demand in 2050 will be 10 times higher than it is now. Furthermore, traditional cooling systems amplify heat stress and the urban heat island effect, leading to a series of adverse health consequences and harming human and animal health. Compared to active cooling (such as electric fans and air conditioners), effective passive radiative cooling technology is considered a green and environmentally friendly cooling method. It involves no energy consumption and transfers heat to the cold outer space through an atmospheric transfer window between 8 and 13 μm. For example, at an ambient temperature of 300 K, the surface of a blackbody on Earth can release about 35% of the energy in the atmospheric window (8-13 μm), which is equivalent to 160 W / m². 2 In 2014, Raman et al. fabricated an integrated photonic radiation cooler and experimentally demonstrated radiation cooling for the first time. This cooler consists of seven alternating layers of HfO2 and SiO2, situated atop an Ag reflective layer. The photonic radiator achieved 97% solar reflectivity and strong infrared emissivity, with a cooling power of 40 W / m² when directly exposed to sunlight. −2 In 2017, a simple and economical method for daytime radiative cooling was proposed. A clever random glass-polymer hybrid material was created by randomly embedding SiO2 microspheres within a transparent polymer. This material achieved a net daily radiative cooling power of 93 W / m². −2 In 2018, a study reported on a phase-change-based layered porous polymer coating exhibiting excellent passive daytime radiative cooling capabilities, reflecting 96% of sunlight and emitting 97% of infrared radiation. This simple and inexpensive method demonstrated a performance of 93 W / m². −2 The cooling power and ambient temperature drop of 6°C are achieved. Simultaneously, a porous scattering mechanism based on a three-dimensional layered porous structure is proposed for the first time. However, these aforementioned heat sinks typically require silver back coatings and expensive equipment, including vacuum deposition, magnetron sputtering, and electron beam lithography, which severely limits their mass production and large-scale application.
[0003] The introduction of PCMs (Polythermal Modular Modules) into building envelopes offers promising prospects for improving energy efficiency. Studies have discussed various PCM integration technologies within building envelopes to enhance thermal comfort. By leveraging the unique properties of PCMs—their ability to store and release heat—buildings can better regulate their internal temperatures, reducing reliance on traditional heating and cooling systems. This not only contributes to energy conservation but also improves the overall comfort and well-being of occupants. Researchers and experts have been actively exploring the application of PCMs in various building components, including walls, roofs, and windows, to maximize their thermal energy storage capacity and optimize the overall building's energy performance. Furthermore, using PCMs can help alleviate peak energy demand and minimize the strain on the power grid during periods of high energy consumption. This can lead to a more stable and reliable energy supply, reducing the risk of energy shortages and power outages.
[0004] The integration of PCM with radiative cooling materials has become a hot research topic in recent years. Currently, many innovative methods exist to combine PCM and radiative cooling materials to better regulate indoor thermal environments. Yang et al. invented an advanced flexible shape-stabilized PCM with excellent thermal management capabilities by integrating energy storage and passive radiative cooling. Qin et al. proposed a radiative coating that improves cooling performance by incorporating randomly distributed PCM-containing microcapsules into acrylic resin. Temperature measurements showed that this coating outperformed pure radiative cooling coatings, exhibiting enhanced cooling performance and time-buffering effects. Woo et al. applied PCM to a daytime radiative cooling coating, resulting in a temperature drop of 9.0°C. ◦ C, the calculated cooling power is 107.8 W / m 2 These innovative materials indicate a trend towards more compact, flexible, and easy-to-use materials. However, these materials are still in the research stage and have not yet been put into commercial use. Summary of the Invention
[0005] To overcome the shortcomings of the prior art, this invention provides a temperature-adaptive thermally regulated radiation cooling coating, its preparation method, and its application.
[0006] This invention is achieved through the following technical solution: In a first aspect, the present invention provides a temperature-adaptive thermally regulated radiation cooling coating, characterized in that the coating is a ZnO@zif-8 polymer coating, which consists of MOF particles with regular dodecahedral structure, a solar reflectivity of 91.9%, an infrared emissivity of 94.4%, and a size of 8-13 μm.
[0007] Secondly, the present invention provides a method for preparing a temperature-adaptive thermally regulated radiation cooling coating, characterized by comprising the following steps: Step 1: Synthesis of ZnO@zif-8 nanoparticles ZnO nanoparticles were dispersed in deionized water to obtain a ZnO suspension. Simultaneously, 2-methylimidazole was dissolved in N,N-dimethylformamide (DMF) solution and stirred at room temperature to obtain a 2-methylimidazole solution. The ZnO suspension was slowly added dropwise to the 2-methylimidazole solution. The resulting ZnO@zif-8 nanoparticles were collected by centrifugation and finally dried. Step 2: Fabrication of the phase change layer KH550 (3-aminopropyltriethoxysilane) contains both amino and ethoxy groups in its molecular structure. The amino group can undergo a ring-opening reaction with the epoxy group of epoxy resin E-44, thus playing a cross-linking and curing role. Phase change energy storage material microcapsules (1.5g) were mixed with KH550 (0.225g) and epoxy resin E-44 (0.375g) modified with ethyl acetate as a solvent. After stirring for 2 hours, a uniform white emulsion was obtained. The prepared white emulsion was sprayed onto glass and cured at 60°C for 3 hours to obtain the underlying phase change layer. Step 3: Preparation of ZnO@zif-8@PCM The ZnO@zif-8 nanoparticles prepared in step one were mixed with KH550 modified epoxy resin E-44. Ethyl acetate was used as a solvent, and the mixture was stirred for 2 hours to obtain a uniform white emulsion. The prepared white emulsion was sprayed onto the underlying phase change layer prepared in step two, and cured at 60°C for 3 hours to obtain a ZnO@zif-8@PCM polymer coating.
[0008] Preferably, in step one, the ZnO@zif-8 nanoparticles are centrifuged at 7000 r / min for 10 minutes.
[0009] Preferably, in step one, the ZnO@zif-8 particles are dried overnight in an oven at 80°C.
[0010] Preferably, in step two, the curing conditions are curing at 60°C for 3 hours.
[0011] Thirdly, the present invention provides the application of temperature-adaptive thermal regulation radiation cooling coating in the field of passive radiation cooling regulation.
[0012] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention combines radiative cooling technology with room temperature phase change technology. Compared with traditional radiative coolers, the material of this invention can alleviate the problems of overheating during the day and undercooling at night. A metal-organic framework (MOF) material, zif-8, was synthesized by controlling different raw material ratios. It was then combined with incompletely reacted ZnO particles to form ZnO@zif-8 mixed nanoparticles. The radiative cooling coating prepared by the mixed nanoparticles achieved high solar reflectivity (91.9%) and infrared emissivity (94.4%, 8-13 μm). The ZnO@zif-8 polymer coating with regular polyhedral morphology significantly enhanced sunlight scattering. After being combined with the phase change material, it achieved sub-environmental cooling with an average temperature drop of 0.66℃ at night and an average temperature drop of 9.8℃ at noon. This temperature-adaptive material shows great promise in passive radiative cooling regulation and can further expand the application of passive radiative cooling.
[0013] (2) This invention synthesizes a metal-organic framework (MOF) material, zif-8, via a liquid-phase self-assembly method, prepares a ZnO@zif-8 polymer coating, and combines it with a PCM coating to prepare a double-layer coating. This coating has the following advantages: During the day, the radiative cooling material reflects a large portion of solar radiation, reducing the increase in solar heat; simultaneously, the slow melting of the PCM absorbs some heat, achieving a significant cooling effect. At night, the PCM solidifies and stores cold energy, offsetting some of the heat emitted into outer space by the radiative cooling coating in the form of infrared radiation, thus providing a certain degree of heat preservation. Attached Figure Description
[0014] The invention will now be further described with reference to the accompanying drawings.
[0015] Figure 1 Synthesis, morphology, and optical properties characterization of ZnO@ZIF-8; (a) Fourier transform infrared spectra of ZnO@ZIF-8 particles; (b, c) XPS of ZnO@ZIF-8 particles; (d) XRD of ZnO@ZIF-8 particles; (e) Reflectance of ZnO@ZIF-8 particles synthesized with different ratios of ZnO to 2-methylimidazole; (fj) SEM images of ZnO@ZIF-8 particles synthesized with different ratios of ZnO to 2-methylimidazole; (k) Adjustment of ZnO@ZIF-8 particles with binder; (i) Emissivity of ZnO@ZIF-8 particles; Figure 2 For the performance characterization of phase change materials; (a) DSC curve of phase change materials; (b) TG curve of phase change materials; (c) SEM of phase change materials; (d) reflectance of phase change material coatings; (e, f) infrared thermal imaging of ZnO@zif-8 coating and ZnO@zif-8@PCM coating; Figure 3Characterization of the sub-environmental cooling performance of the ZnO@zif-8@PCM coating; (a) Photograph of the cooling performance testing apparatus under sunlight. (b) Schematic cross-section of the experimental apparatus used to test cooling performance. (c) Reflectivity of the final product. (d, e) Sample temperature and ambient air temperature measured during the day in Jinan on August 19, 2025. (f, g) Sample temperature and ambient air temperature measured at night in Jinan from August 19 to 20, 2025. (h) Contact angle of water droplets on the ZnO@zif-8@PCM coating. Detailed Implementation
[0016] The invention will now be further described with reference to the accompanying drawings.
[0017] Example 1 Material All chemicals and solvents were available from commercial suppliers without further purification. Deionized water (18.4 MΩ) used in all experiments was obtained from a water purification system. Nano zinc oxide (99.9% metalsbasis, 200nm), 2-methylimidazole (98%), epoxy resin E-44, 3-aminopropyltriethoxysilane (99%), N,N-dimethylformamide (>99.9% GC), and ethyl acetate (99.7%) were purchased from Shanghai Maclean Biochemical Technology Co., Ltd. The phase change energy storage material microcapsules PCM-28 were purchased from Taobao (https: / / m.tb.cn / h.SrXdtN0iSLgrMpW).
[0018] Preparation of ZnO@zif-8@PCM polymer coating Synthesis of ZnO@zif-8 nanoparticles 1 g of ZnO nanoparticles were thoroughly dispersed in 60 mL of deionized water for 30 minutes, while 3 g of 2-methylimidazole was dissolved in 180 mL of N,N-dimethylformamide solution and stirred at room temperature for 24 hours. The dispersed ZnO suspension was slowly added dropwise to the 2-methylimidazole solution, and the resulting ZnO@zif-8 nanoparticles were collected by centrifugation at 7000 r / min for 10 minutes. Finally, the ZnO@zif-8 particles were dried overnight in an oven at 80°C.
[0019] Fabrication of phase change layers Purchased polymethyl methacrylate (PMMA) encapsulated octadecane phase change energy storage material microcapsules PCM-28 (1.5 g) were mixed with KH550 (0.225 g) modified epoxy resin E-44 (0.375 g) (modification method cited in Xia, Yingjie, et al. "Development and mechanical properties of nano SiO2 modified photosensitive resin for high-strength and high-brittleness 3Dprinting in rock reconstruction." Construction and Building Materials 450(2024): 138685.), dispersed in ethyl acetate (10 mL), and stirred for 2 hours to obtain a uniform white emulsion. The prepared white emulsion was sprayed onto glass and cured at 60°C for 3 hours to obtain the bottom phase change layer.
[0020] Preparation of ZnO@zif-8@PCM KH550 (3-aminopropyltriethoxysilane) contains two active groups, amino and ethoxy, in its molecular structure. The amino group can undergo a ring-opening reaction with the epoxy group of epoxy resin E-44, thereby playing a cross-linking and curing role. ZnO@zif-8 nanoparticles (1.5 g) were prepared, and epoxy resin E-44 modified with KH550 (0.28 g, 0.47 g of modified epoxy resin E-44) was used as a binder to manufacture the ZnO@zif-8 polymer coating. The above materials (ZnO@zif-8 nanoparticles, KH550 modified epoxy resin E-44) were dispersed in ethyl acetate (8 mL). After stirring for 2 hours, a uniform white emulsion was obtained. The prepared coating was sprayed onto the prepared phase change layer and cured at 60°C for 3 hours to obtain the ZnO@zif-8@PCM polymer coating.
[0021] Characterization methods The crystal structure of ZnO@zif-8 was measured using X-ray diffraction (XRD). The morphology and structure of ZnO@zif-8 nanoparticles with different particle sizes were characterized by scanning electron microscopy (SEM). The solar reflectance of the coating was measured by UV / VIS / NIR spectrometry in the range of 300–2500 nm. The thermal emissivity of the coating was measured by Fourier transform infrared spectroscopy in the range of 3–20 μm and 400–4000 nm. -1 The chemical structure of the prepared coating was characterized by Fourier transform infrared spectroscopy (FT-IR) within a certain range. The apparatus for evaluating radiative cooling performance consisted of a box made of insulating foam material coated with a ZnO@zif-8@PCM polymer coating and another coating made of glass. Temperature differences were recorded using ordinary thermocouples at noon and evening to indirectly evaluate the radiative cooling performance. XPS was used to confirm the synthesis of ZnO@zif-8 nanoparticles. The phase change energy storage material microcapsules were characterized by thermogravimetric analysis (TG) and differential scanning calorimetry (DSC).
[0022] Example 2 Results and Discussion Synthesis, morphology and optical properties of ZnO@zif-8 like Figure 1 As shown in Figure a, this invention first demonstrates the successful synthesis of ZnO@zif-8 using Fourier transform infrared spectroscopy (FTIR). An absorption peak appears near 422 cm⁻¹ in the FTIR spectrum, attributed to the Zn-N stretching vibration. This peak confirms the presence of Zn in the 2-methylimidazolium salt ligand. 2+ The coordination between nitrogen atoms indicates that 2-methylimidazole successfully reacted with zinc oxide to generate zif-8. Figure 1 b and 1c show the XPS results, where Zn and N elements were primarily analyzed in the measured spectra. In the N 1s spectrum ( Figure 1 (b) The peak at 399.0 eV is attributed to the N atom in the imidazole, and the peak at 400.7 eV belongs to the N atom in the Zn–N bond. In the Zn 2p spectrum ( Figure 1 c), the double peaks at 1021.4 (2p3 / 2) eV and 1039.0 (2p1 / 2) eV belong to Zn atoms in the Zn–N bond, and the peaks at 1021.3 (2p3 / 2) eV and 1044.3 (2p1 / 2) eV are attributed to Zn atoms in the Zn-O bond. This indicates that the successful synthesis of Zif-8 is related to the presence of ZnO, suggesting that ZnO did not react completely, and the final product is a mixture of ZnO@zif-8. ZnO@zif-8 nanoparticles were prepared via a liquid-phase self-assembly method, and the XRD pattern of the crystals (…) Figure 1The peak profile of ZnO@zif-8 in d) is in excellent agreement with the simulated XRD patterns of ZnO and Zif-8, further confirming that the final particles are a mixture of ZnO and Zif-8. Passive radiative cooling is a physical process that achieves the "passive outward transfer" of heat from the surface of an object without consuming external energy such as electrical or chemical energy, relying solely on the optical properties of the material itself and the laws of the natural environment. It mainly reduces its own heat by reflecting sunlight in the 0.3-2.5µm range to minimize solar thermal gain and radiating heat into outer space through atmospheric transparency in the 8-13µm range. Because Zif-8 has a special dodecahedral structure, the ZnO@zif-8 polymer coating has high reflectivity and can effectively reflect sunlight. Figure 1 (e) The optimal ZnO@zif-8 coating was prepared by varying the ratio of ZnO to 2-methylimidazole. Figures (1f-1j) show SEM images of the particles. By continuously increasing the ratio of 2-methylimidazole, the synthesized Zif-8 particles first decreased and then increased in size, reaching their smallest size (approximately 2.5 μm) at a ZnO:2-methylimidazole ratio of 1:3, where the reflectivity was highest. This is because the coating primarily reflects visible light (380-760 nm) and near-infrared light (760-2500 nm). Therefore, the closer the particle size is to the 0.3-2.5 μm range, the easier it is to achieve an "optimal interaction ratio" with these two types of light wavelengths, resulting in higher reflectivity. After determining the optimal synthesis ratio, the optimal reflectivity ratio (2k) was found by varying the ratio of particles to binder. The atmospheric transparency window (8-13 μm) is a key medium for radiative cooling, as thermal emission can dissipate heat into outer space. Therefore, the radiative cooling capability largely depends on the emissivity of the ZnO@zif-8 polymer coating. Calculations show that the coating has an average emissivity greater than 0.9, and a thermal emissivity of 0.944, particularly within the atmospheric transparency window (8-13 μm). Figure 1 i) The strong infrared emissivity of the coating in the 8-13 μm range is mainly attributed to molecular vibrations and stretching; the 995 cm⁻¹ and 1147 cm⁻¹ ranges are due to CN stretching vibrations, while the 1432 cm⁻¹ range is due to intra-ring skeletal vibrations of the imidazole ring. Based on the above analysis, the ZnO@ZIF-8 polymer coating, as an excellent material for daytime radiative cooling, has great potential in building energy conservation.
[0023] Performance of phase change materials Considering the practical applications of phase change materials, this invention studies the phase change layer. DSC (differential scanning calorimetry) and TG (thermogravimetric analysis) indicate that the phase change material possesses both heat storage and heat release properties. Figure 2a and 2b). Scanning electron microscopy (SEM) images reveal the morphology of the phase change material ( Figure 3 c) The optimal ratio between the phase change coating and the radiation cooling coating was found by measuring the reflectivity of the phase change coating. Figure 3 d). To study the heat storage and heat release properties of phase change materials, a ZnO@ZIF-8 coating with and without phase change materials was applied ( Figure 3 e) with ZnO@zif-8@PCM coating containing phase change material ( Figure 3 f) Placed at 40 ◦ A heating platform was used, and an infrared camera was employed to monitor the surface temperature in real time. The temperature of the ZnO@ZIF-8 coating rose faster than that of the ZnO@ZIF-8@PCM coating. Upon reaching the phase transition point, ZnO@ZIF-8@PCM absorbed heat, resulting in a slower temperature rise. The maximum temperature difference between the two coatings reached 10°C after 20 seconds. ◦ C. Based on the above results, it can be concluded that the double-layer ZnO@zif-8@PCM coating with phase change material has an exceptional buffering capacity for high-temperature environments. This capacity is beneficial for temperature adaptation management and provides a comfortable environment.
[0024] Sub-environmental cooling performance of ZnO@zif-8@PCM coating To further evaluate the radiative cooling performance of the ZnO@zif-8@PCM polymer coating, outdoor experiments were conducted. From August 19th to 20th, 2025, the radiative cooling performance of the coating was tested in Jinan, China. A schematic diagram of the experimental setup is shown in the figure. Figure 3 a and Figure 3 As shown in b), the reflectance of the final product with the ZnO@zif-8@PCM polymer coating is shown in the figure. Figure 3 c). Figure 3 d and Figure 3 e) shows the temperature data recorded between 10:00 AM and 2:00 PM. It can be seen that under the same conditions, the ZnO@zif-8@PCM polymer coating is always cooler than the glass, with a maximum ambient temperature decrease of 11.2°C and an average decrease of approximately 9.8°C. Compared to other previously reported radiative cooling materials, the coating designed in this invention exhibits excellent cooling performance, effectively reducing the temperature of objects under direct sunlight and demonstrating effective daytime radiative cooling performance. Figure 3 f and Figure 3 (g) Temperature data recorded between 12:00 AM and 4:00 AM showed that the overall temperature of the coating was only 0.66°C lower than the average ambient temperature, a relatively small decrease, indicating a good insulation effect. Therefore, this polymer coating can alleviate the problem of overheating during the day and excessive cooling at night, and has great potential in managing passive radiative cooling performance. Figure 3g) The surface coating has a self-cleaning function.
Claims
1. A temperature-adaptive thermally regulated radiation cooling coating, characterized in that, The coating has a solar reflectivity of 91.9%, an infrared emissivity of 94.4%, and a micrometer size of 8-13 μm. A method for preparing a temperature-adaptive thermally regulated radiation-cooled coating includes the following steps: Step 1: Synthesis of ZnO@zif-8 nanoparticles 1 g of ZnO nanoparticles were dispersed in 60 mL of deionized water for 30 min to obtain a ZnO suspension. Simultaneously, 3 g of 2-methylimidazole was dissolved in 180 mL of N,N-dimethylformamide solution and stirred at room temperature for 24 h to obtain a 2-methylimidazole solution. The ZnO suspension was slowly added dropwise to the 2-methylimidazole solution to carry out the reaction. The ZnO@zif-8 nanoparticles obtained from the reaction were collected by centrifugation. Finally, the ZnO@zif-8 particles were dried in an oven at 80 °C. Step 2: Fabrication of the phase change layer First, 0.225g of KH550 and 0.375g of epoxy resin E-44 were mixed and modified. Then, 1.5g of phase change energy storage material microcapsules were added and dispersed in 10mL of ethyl acetate. After stirring for 2 hours, a uniform white emulsion was obtained. The prepared white emulsion was sprayed onto glass and cured at 60°C for 3 hours to obtain the bottom phase change layer. Step 3: Preparation of ZnO@zif-8@PCM First, KH550 was modified by mixing with epoxy resin E-44. Then, the ZnO@zif-8 nanoparticles prepared in step one were added. Using 8 mL of ethyl acetate as solvent, the mixture was stirred for 2 hours to obtain a uniform white emulsion. The prepared white emulsion was sprayed onto the phase change layer prepared in step two and cured at 60°C for 3 hours to obtain a ZnO@zif-8@PCM polymer coating.
2. The temperature-adaptive thermally regulated radiation cooling coating according to claim 1, characterized in that, In step one, the ZnO@zif-8 nanoparticles were centrifuged at 7000 r / min for 10 minutes.
3. The temperature-adaptive thermally regulated radiation cooling coating according to claim 1, characterized in that, In step one, ZnO@zif-8 particles are dried overnight in an oven at 80°C.
4. The temperature-adaptive thermally regulated radiation cooling coating according to claim 1, characterized in that, In step two, the curing conditions are 60°C for 3 hours.
5. The application of the temperature-adaptive thermal regulation radiation cooling coating according to any one of claims 1-4 in the field of passive radiation cooling regulation.
Citation Information
Patent Citations
Passive radiation cooling composite coating and preparation method
CN116120794A
PLA radiation cooling fiber membrane with antibacterial performance and preparation method of PLA radiation cooling fiber membrane
CN119194736A